Study the effect of doping withCa2+ and Si4+ ions on linear absorption coefficient of garnet ferrite film using Saha Equation (Latakia University Journal -Basic Sciences Series, 2020)
In this work the preparation of garnet ferrite film using Sol-Gel method have been presented. Then, films are doped with Ca2+ and Si4+ ions where the references studies show that the both two ions whose roles are acceptors and donors, respectively for iron ions containing in ferrite structure. That why, we have carried out computerized study for ionized Ca and Si ratios as a function of temperature T, and effect of temperature on partition function for both ions.This study shows that Ca2+ ratio increases gradually from 5250 K while for Si4+ ration has a sharped increase at temperature of T=7200 K. According partition function of Ca and Si the effect of temperature appears at 15000 K for Ca and 20000 K for Si.